Simulation of dispersed phase evolution for immiscible polymer blends in injection molding. Issue 7 (2nd October 2017) - Chen, Dan; Liu, Fen; Zhang, Yi; Zhang, Yun; Zhou, Huamin
Abstract : Purpose: The numerical simulation of dispersed-phase evolution in injection molding process of polymer blends is of great significance in both adjusting material microstructure and improving performances of the final products. This paper aims to present a numerical strategy for the simulation of dispersed-phase evolution for immiscible polymer blends in injection molding. Design/methodology/approach: First, the dispersed-phase modeling is discussed in detail. Then the Maffettone–Minale model, affine deformation model, breakup model and coalescence statistical model are chosen for the dispersed-phase evolution. A general coupled model of microscopic morphological evolution and macroscopic flow field is constructed. Besides, a stable finite element simulation strategy based on pressure-stabilizing/Petrov–Galerkin/streamline-upwind/Petrov–Galerkin method is adopted for both scales. Findings: Finally, the simulation results are compared and evaluated with the experimental data, suggesting the reliability of the presented numerical strategy. Originality/value: The coupled modeling of dispersed-phase and complex flow field during injection molding and the tracing and simulation of droplet evolution during the whole process can be achieved.